RETROKAVAL (SİRKUMKAVAL) ÜRETER: OLGU SUNUMU - ATAKAN, İrfan Hüseyin and KAYA, Esat and ALAGÖL, Bülent and KAPLAN, Mustafa and İNCİ, Osman (Cerrahpaşa Medical Journal, 2014)
Background.. Retrocaval ureter is a rare entity that causes dysfunction of the effected kidney and is at times hard to diagnose. Observation.- A rare right retrocaval (circumcaval) ureter case leading to hydronephrosis has been presented and the types, diagnosis and the treatment of this entity has been discussed.